Review: Spektrofotometri UV-VIS dalam Penentuan Nilai SPF pada Tabir Surya Ekstrak Alam - Irtiza Inayatur Rahman; Delima Delima; Lasya Ananga NurFauziyya; Lingga Lingga; La Ode Akbar Rasydy (Jurnal Kesehatan Amanah, 2025)
Indonesia is a tropical country with high sun exposure every year. Sunlight has radiation that is bad for skin health, especially ultraviolet (UV) rays. Without protection, these rays have the potential to cause skin damage such as erythema, hyperpigmentation, premature aging, and even skin cancer. The use of sunscreen is an effort to protect the skin because it has a protective power expressed as Sun Protection Factor (SPF), the SPF value can be determined by using the UV-Vis spectrophotometric method. The purpose of this study is to explain the application of the UV-Vis spectrophotometric method in determining the SPF value in natural extract-based sunscreen preparations. The methodology used was a literature study of the last 10 years. The results of this study indicate that the application of UV-Vis spectrophotometric method is very effective and efficient to measure the sun protection value (SPF) of natural extracts. The analysis showed significant variation in SPF values of various plant extracts, with kecombrang (Etlingera elatior) flower extract recording the highest value (106.8) in the ultra of sunscreen protection category, while jejuru leaf extract showed effectiveness in the minimal protection category (3.8478). This study makes an important contribution in exploring the potential of local materials for sustainable sunscreen formulations.